PENINGKATAN PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG PHBS DALAM PENCEGAHAN DAN PENANGANAN Covid-19 - Yogopriyatno, Jatmiko; Suratman, Suratman (JURNAL PENGABDIAN RAFFLESIA ADMINISTRASI PUBLIK, 2022)
Seeing the various realities and phenomena that exist in the field regarding the spread of the spread of the corona virus case (Covid-19) in Indonesia, it has spread in all provinces, including Bengkulu Province. With this condition, it becomes necessary for academics to increase knowledge, attitudes and understanding of the community in Sunda Kelapa Village, Pondok Kelapa District, Central Bengkulu Regency regarding PHBS as the first step and form Village Volunteers to Fight Covid-19 in carrying out their activities and activities with the principle of gotong royong involving support from villagers as a second step. The method of activity consists of; first, second lecture activities, discussion and question and answer activities and third, pre-test activities. Some conclusions that can be drawn from this Service activity are; (a) Increasing knowledge and attitudes of the community through counseling and providing booklets on PHBS in the Prevention and Handling of Covid-19 carried out according to the theme of the Bengkulu University Thematic Service program, there are differences in the level of knowledge and attitudes of the community before and after the booklet is given. (b) Cooperation with village officials is very important to facilitate the implementation of the program for the formation of Village Volunteers Against Covid-19. The suggestions from this service activity are; (a) There needs to be ongoing socialization from the village regarding PHBS in the Prevention and Handling of Covid-19 in Sunda Kelapa Village, and (b) Community participation is needed for the success of the PHBS program in the Prevention and Handling of Covid-19 in Sunda Kelapa Village.